Sugar Level Detection Using Thermal Images - Suresh Anand, M; Balamurugan, M; Shubathra, R; Ragavi, M; Bhagya Lakshmi Priya, R (International Journal of Engineering and Technology, 2018)
Diabetes mellitus, commonly called as Diabetes, in which the person has high sugar level. Insulin, produced by the pancreas, is responsible for controlling the level of blood glucose level. The lack of production in insulin leads to Diabetes. If the problem left untreated, it leads to serious complications includes cardiac problems. There are various invasive techniques to diagnose diabetes. In this project we are using mid infrared rays instead of near infrared rays to acquire the thermal image of the palm. The thermal imagesÂ are pre-processed and segmented using k means clustering. Then they are subjected to feature extraction and then classified using classifiers. The classifiers like SupportVectorMachine(SVM),ProbabilisticNeural Network(PNN),K-Nearest Neighbour Network (KNN) are used to diagnose the thermal images of palm.Â Â